2021
DOI: 10.3389/fpls.2021.765357
|View full text |Cite
|
Sign up to set email alerts
|

Ethephon-Mediated Bloom Delay in Peach Is Associated With Alterations in Reactive Oxygen Species, Antioxidants, and Carbohydrate Metabolism During Dormancy

Abstract: Ethephon (ET) is an ethylene-based plant growth regulator (PGR) that has demonstrated greater efficacy in delaying bloom in deciduous fruit species. However, the underlying mechanisms by which ET modulates dormancy and flowering time remain obscure. This study aimed to delineate the ET-mediated modulations of reactive oxygen species (ROS), antioxidants, and carbohydrate metabolism in relation to chilling and heat requirements of “Redhaven” peach trees during dormancy. Peach trees were treated with ethephon (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Previous studies indicate that the accretion of ROS, coupled with antioxidant scavenging mechanisms, is essential for the release of endodormancy and ecodormancy [ 16 , 19 ]. Consistently, our recent study [ 3 ] showed the ET treatment induces higher levels of ROS (e.g., singlet oxygen and hydrogen peroxide) and the elevated activity of ROS-generating enzymes (e.g., NADPH-oxidase and superoxide dismutase), as well as scavenging enzymes (e.g., catalase and glutathione peroxidase) during endodormancy. In this study, the ET-induced expression shift of genes that are related to antioxidant activities confirmed the above findings and also signified the effects of ET in modulating ROS levels, which altered the phenology of dormancy and flowering.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous studies indicate that the accretion of ROS, coupled with antioxidant scavenging mechanisms, is essential for the release of endodormancy and ecodormancy [ 16 , 19 ]. Consistently, our recent study [ 3 ] showed the ET treatment induces higher levels of ROS (e.g., singlet oxygen and hydrogen peroxide) and the elevated activity of ROS-generating enzymes (e.g., NADPH-oxidase and superoxide dismutase), as well as scavenging enzymes (e.g., catalase and glutathione peroxidase) during endodormancy. In this study, the ET-induced expression shift of genes that are related to antioxidant activities confirmed the above findings and also signified the effects of ET in modulating ROS levels, which altered the phenology of dormancy and flowering.…”
Section: Discussionsupporting
confidence: 85%
“…However, ethephon (ET) application often causes mild to moderate injuries to peach trees, such as gummosis, floral bud death, and dieback of the branches, which limit the utility of ET. Our recent investigations have also indicated that ET may affect flowering phenology in peach through modulating the progression of bud dormancy, which is subject to the influences of phytohormone fluctuation, oxidative pressure, and carbohydrate metabolism [ 2 , 3 ]. An increased understanding of the mechanisms by which ET induces bloom delay is fundamental to developing effective strategies to combat spring frost and elucidate potential mechanisms of injury that can be ameliorated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its application varies across plant species depending on the time of application and the concentration used (Li and Solomon, 2003). Ethylene has been implicated in plant growth inhibition, enhancing germination rate, inducing and repressing flowering, affecting secondary metabolites production, herbicide efficacy augmentation, pollen sterility induction, enhancing fruit quality and fruit ripening, pests eradication, delaying bloom in deciduous fruits, increasing chlorophyll, proline, peroxidases content and enhancing yield in a wide range of crops (Sun et al, 2015;Cunha et al, 2017;Iqbal et al 2017;Jain et al, 2018;Islam et al, 2021;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%